Assessment of thrombus length in acute ischemic stroke by post-contrast magnetic resonance angiography. (18th November 2017) - Ganeshan, Ramanan; Nave, Alexander H; Scheitz, Jan F; Schindlbeck, Katharina A; Haeusler, Karl Georg; Nolte, Christian H; Villringer, Kersten; Fiebach, Jochen B
Abstract : Objectives: Post-contrast magnetic resonance angiography (PC-MRA) enables visualization of vessel segments distal to an intra-arterial thrombus in acute ischemic stroke. We hypothesized that PC-MRA also allows clot length measurement in different intracranial vessels. Methods: Patients with MRI-confirmed ischemic stroke and intracranial artery occlusion within 24 hours of symptom onset were prospectively evaluated. PC-MRA was added to a standard stroke MRI protocol. Thrombus length was measured on thick slab maximum intensity projection images. Clinical outcome at hospital discharge was assessed by modified Rankin Scale (mRS). Results: Thirty-four patients (median age 72 years) presenting with a median National Institutes of Health Stroke Scale score of 11 and a median onset to imaging time of 116 min were included. PC-MRA enabled precise depiction of proximal and distal terminus of the thrombus in 31 patients (91%), whereas in three patients (9%) PC-MRA presented a partial occlusion. Median thrombus length in patients with complete occlusion was 9.9 mm. In patients with poor outcome (mRS ≥3) median thrombus length was significantly longer than in those with good outcome (mRS ≤2;P=0.011). Conclusions: PC-MRA demonstrates intra-arterial thrombus length at different vessel occlusion sites. Longer thrombus length is associated with poor clinical outcome. Clinical trial registration: NCT02077582; Results.